PENGGUNAAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS ARTICULATE STORYLINE 3 PADA SISWA SD - Firda Alviyanti; Waspodo Tjipto Subroto; Nasution (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to identify, obtain and examine the use of interactive learning media based on Articulate Storyline 3 among elementary school students. The method used in this research is the literature review method, starting with collecting information from articles, books and scientific works that are relevant to the research theme. Research results show that interactive learning media based on Articulate Storyline 3 helps students understand the material. Interactive media-based learning allows students to interpret or make their own conclusions about what they learn. The research results show that interactive learning media based on Articulate Storyline 3 plays an important role in the modern education process.